The effect of mixing peatland burning remains as fly ash and peat soil on its California Bearing Ratio value. (December 2019) - Ramdhiani, E; Rahayu, W
Abstract: Peat has been known for its high compressibility, low shear strength and high-water content. Moreover, when it comes to dry season, peat can easily be burnt leaving the large amount of carbon into the atmosphere also causes significant damage to peatland ecology. Based on these, peat burning remains are used as fly ash and it is expected to improve the strength of peat soils alongside to be environmentally safe. Laboratory tests were carried out according to that condition. A study on the influence of fly ash addition in peat soils was done by comparing the result from CBR (California Bearing Ratio). Different percentages of fly ash (i.e. 15, 20, and 25%) were added into peat soil at optimum moisture content amidst 5% of Portland cement for each sample with a variety of curing time of 2 hours, 1 day, 3 days, and 7 days. Changes were observed in specific gravity, acidity, and the microscopic structure. The CBR test results show that the peat gained strength due to the addition of fly ash, with the optimum result of 5.36% for unsoaked condition and 6.35% for soaked condition. Furthermore, according to the results, the peat soil can be used as a subgrade.